Barriers for women in career advancement: the perception of female employees in Zecon Berhad (ZB)/ Syazwan Abu Samah - Abu Samah, Syazwan (2016)
This study was about Barriers for Women in Career Advancement: The Perception of Female Employees in Zecon Berhad (ZB). There were two objectives for this study which the first objective was Perception of Employees toward Women Career Advancement in Zecon Berhad and the second objective was Major Barriers for Women Career Advancement in Zecon Berhad. The method that been used by the researcher to conducted this study was descriptive method study. Furthermore, the respondents will be the non-executive female employees in Zecon Berhad. This study used a set of questionnaire to collected data as their primary instrument. The questionnaire consisted of three sections: for Section A, it focused on the respondents general information, for Section B, it focused on the perception of employees toward women career advancement and lastly for Section C it focused on major barriers for women career advancement. Based on the results of findings, result found that most of the respondents perceived that family responsibilities were one of the major barriers for women to be a leader in an organization with the highest total mean which was (M=3.79, SD=0.789) for first objective, and for second objective, most respondents agreed that lack of equal career development opportunities for women with total mean of (M=3.64, SD=1.104) was the major barrier for women career advancement in Zecon Berhad. As the conclusion, for future research, the researcher can expand the sample size of the respondents for both gender male and female. Plus, they can also use other types of instrument to gather their data for example they can use interviews or direct observation for their instrument.